Management of Women With an Unexpected Low Ovarian Response to Gonadotropin - Conforti, Alessandro; Esteves, Sandro C.; Cimadomo, Danilo; Vaiarelli, Alberto; Di Rella, Francesca; Ubaldi, Filippo Maria; Zullo, Fulvio; De Placido, Giuseppe; Alviggi, Carlo (Frontiers in Endocrinology, 2019)
POSEIDON groups 1 and 2 patients respond poorly (<4 oocytes retrieved) or sub-optimally (4-9 oocytes retrieved) to gonadotropin stimulation despite the presence of adequate ovarian parameters, which negatively affect their cumulative chances of delivering a baby using Assisted Reproductive Technology. A polygenic trait involving gonadotropins and/or their receptors seems to be the primary pathophysiology mechanism explaining this phenomenon. The clinical management is mainly focused on maximizing oocyte yield as to increase the likelihood of having at least one euploid embryo for transfer. Indices such as FORT (follicle output rate) and FOI (follicle-to-oocyte index) may be used to determine if the ovarian reserve was properly explored during a previous ovarian stimulation. Testing for the presence of common polymorphisms affecting gonadotropins and/or their receptors can also be considered before starting stimulation as a means to identify patients at risk of hypo-response. An individualized estimation of the minimum number of oocytes needed to obtain at least one euploid embryo can assist counseling and treatment planning. Among currently existing pharmacological interventions, use of recombinant FSH in preference over urinary gonadotropin preparations, FSH dosage increase, and use of rLH supplementation may be considered -alone or combined- for optimally managing POSEIDON’s groups 1 and 2 patients. However, given the recent introduction of the POSEIDON criteria, there is still a lack of studies examining the role of interventions specifically to patients classified as groups 1 and 2, thus making it an area for open research.